Job Satisfaction and Turnover Intention among Travel Agency Employees in Selangor - Mohd Tobi, Siti Noraini; Norizan, Juliana; Besir, Mohamad Shahril Mohamad; Abdul Aziz, Nor Intan Shamimi; Kadang, Hendrikus (Information Management and Business Review, 2024)
Job satisfaction is among the most difficult issues for many business leaders to address. Researchers have widely discussed this problem, yet statistics still show an alarming increase, and various factors cause it to happen often. This study aims to examine the relationship between job satisfaction and turnover intention and investigate the moderating effect of employee gender and years of experience on the relationship. The four workplace satisfaction determinants—career advancement, employee empowerment, pay level, and nature of the work—that affect employee turnover intention are covered in this study. This study involved respondents among the travel agencies’ employees within the state of Selangor, regardless of their working position. A set of questionnaires was distributed to 130 employees from 26 travel agency companies that participated in the study. The results show employee empowerment has a significant negative relationship with turnover intention. It has been also found that the relationship between job satisfaction and turnover intention is significantly moderated by gender and years of experience. This study recommends that further research should use a larger sample size and qualitative methods to gain comprehensive knowledge regarding the phenomenon.